2021
DOI: 10.3390/molecules26144242
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Porcine NK-Lysin: A Novel Immunomodulator That Regulates Intestinal Inflammatory Response

Abstract: Porcine NK-Lysine (PNKL) is a new antimicrobial peptide (AMP) identified in the small intestine. In this study, PNKL protein was obtained through heterologous expression in Escherichia coli and was estimated by SDS-PAGE at 33 kDa. The antibacterial activities of PNKL were determined using various bacterial strains and showed broad-spectrum antimicrobial activity against Gram-negative and Gram-positive bacteria. Furthermore, E. coli K88-challenged IPEC-J2 cells were used to determine PNKL influences on inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 70 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…Han et al found that defensin pBD2 could increase the gene expression of ZO-1 and Occludin in mouse colon, and relieve the colon inflammation induced by DSS in mice (Han et al, 2015). Lin et al found that E.coli K88 lead to a decrease in the expression of tight junction protein ZO-1 in IPEC-J2 cells, and the antimicrobial peptide orcine NK-Lysine (PNKL) could significantly increase the expression of tight junction protein ZO-1 (Lin et al, 2021). The above results suggest that MPX can increase the expression of intestinal tight junction proteins and enhance the intestinal epithelial barrier.…”
Section: Discussionmentioning
confidence: 95%
“…Han et al found that defensin pBD2 could increase the gene expression of ZO-1 and Occludin in mouse colon, and relieve the colon inflammation induced by DSS in mice (Han et al, 2015). Lin et al found that E.coli K88 lead to a decrease in the expression of tight junction protein ZO-1 in IPEC-J2 cells, and the antimicrobial peptide orcine NK-Lysine (PNKL) could significantly increase the expression of tight junction protein ZO-1 (Lin et al, 2021). The above results suggest that MPX can increase the expression of intestinal tight junction proteins and enhance the intestinal epithelial barrier.…”
Section: Discussionmentioning
confidence: 95%
“…Morroni G et al found that the antimicrobial peptide LL-37 has good antibacterial activity against multidrug-resistant E. coli, and MIC and sub-MIC concentrations of LL-37 were able to reduce E. coli bio lm formation [21]. Vergis J et al found that the antimicrobial peptide lactoferricin (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) has good antibacterial and antibio lm activity against multidrug-resistant enteroaggregative E. coli, and lactoferricin (17-30) signi cantly reduced the formation of E. coli bio lms [22]. Mishra BE et al found that the antimicrobial peptide WW298 could effectively inhibit MRSA attachment and disrupt its preformed bio lms more effectively than daptomycin [23].…”
Section: Discussionmentioning
confidence: 99%
“…Han et al found that defensin pBD2 could increase the gene expression of ZO-1 and Occludin in the mouse colon and relieve the colon in ammation induced by DSS in mice [29]. Lin et al found that E. coli K88 led to a decrease in the expression of the tight junction protein ZO-1 in IPEC-J2 cells, and the antimicrobial peptide porcine NK-Lysine (PNKL) signi cantly increased the expression of the tight junction protein ZO-1 [30]. The above results suggest that MPX can increase the expression of intestinal tight junction proteins and enhance the intestinal epithelial barrier.…”
Section: Mpx Inhibits E Coli Bio Lm Formationmentioning
confidence: 99%
“…It was observed that PNKL led to a decrease in the expressions of inflammatory cytokines IL-6, NF-κB, TNF-α, Caspase-3, and Caspase-9 in the E. coli K88-challenged cells. These properties offer PNKL to be a substitute for some antibiotics [ 42 ]. AMP production using (clustered regularly interspaced short palindromic repeats) CRISPR technology was tried out in Bombyx mori cells; CRISPR/Cas9 could successfully induce site-specific mutation of the cactus gene that could produce AMPs through gene editing [ 56 ].…”
Section: Mechanism Of Action Of Ampsmentioning
confidence: 99%